Water Intake and Hydration Indices in Healthy European Adults: The European Hydration Research Study (EHRS) - Malisova, Olga (Nutrients, 2016)
Hydration status is linked with health, wellness, and performance. We evaluated hydration status, water intake, and urine output for seven consecutive days in healthy adults. Volunteers living in Spain, Germany, or Greece (n = 573, 39 ± 12 years (51.1% males), 25.0 ± 4.6 kg/m(2) BMI) participated in an eight-day study protocol. Total water intake was estimated from seven-day food and drink diaries. Hydration status was measured in urine samples collected over 24 h for seven days and in blood samples collected in fasting state on the mornings of days 1 and 8. Total daily water intake was 2.75 ± 1.01 L, water from beverages 2.10 ± 0.91 L, water from foods 0.66 ± 0.29 L. Urine parameters were: 24 h volume 1.65 ± 0.70 L, 24 h osmolality 631 ± 221 mOsmol/kg Η(2)Ο, 24 h specific gravity 1.017 ± 0.005, 24 h excretion of sodium 166.9 ± 54.7 mEq, 24 h excretion of potassium 72.4 ± 24.6 mEq, color chart 4.2 ± 1.4. Predictors for urine osmolality were age, country, gender, and BMI. Blood indices were: haemoglobin concentration 14.7 ± 1.7 g/dL, hematocrit 43% ± 4% and serum osmolality 294 ± 9 mOsmol/kg Η(2)Ο. Daily water intake was higher in summer (2.8 ± 1.02 L) than in winter (2.6 ± 0.98 L) (p = 0.019). Water intake was associated negatively with urine specific gravity, urine color, and urine sodium and potassium concentrations (p < 0.01). Applying urine osmolality cut-offs, approximately 60% of participants were euhydrated and 20% hyperhydrated or dehydrated. Most participants were euhydrated, but a substantial number of people (40%) deviated from a normal hydration level.